Panentheism and Panpsychism Philosophy of Religion Meets Philosophy of Mind - Brüntrup, Godehard; Göcke, Benedikt Paul; Jaskolla, Ludwig; Tapp, Christian; Niederbacher, Bruno (Innsbruck Studies in Philosophy of Religion, 2020)
Panpsychism has become a highly attractive position in the philosophy of mind. On panpsychism, both the physical and the mental are inseparable and fundamental features of reality. Panentheism has also become immensely popular in the philosophy of religion. Panentheism strives for a higher reconciliation of an atheistic pantheism, on which the universe itself is causa sui, and the ontological dualism of necessarily existing, eternal creator and contingent, ﬁnite creation. Historically and systematically, panpsychism and panentheism often went together as essential parts of an allembracing metaphysical theory of Being. The present collection of essays analyses the relation between panpsychism and panentheism and provides critical reﬂections on the signiﬁcance of panpsychistic and panentheistic thinking for recent debates in philosophy and theology.